Error analysis of the orthogonal parallel calibration device for six-axis heavy force sensor. Issue 4 (May 2019) - Lin, Sheng; Sun, Liguang
Abstract: An orthogonal parallel mechanism is employed to design the calibration device for six-axis heavy force sensor. The relationship between the input and output is proposed. The kinematics error of the orthogonal parallel mechanism is analyzed. The influence of the hinges and the electric cylinders on the calibration accuracy is calculated. The fixture positioning error is analyzed. All the results provide the theory evidence for the manufacture and assembling to reduce the calibration error.